Household costs incurred under community- and facility-based service-delivery models of tuberculosis preventive therapy for children: a survey in Cameroon and Uganda - Mafirakureva, Nyashadzaishe; Mukherjee, Sushant; Tchounga, Boris; Atwine, Daniel; Tchakounte Youngui, Boris; Ssekyanzi, Bob; Okello, Richard; Leonie, Simo; Cohn, Jennifer; Casenghi, Martina; Vasiliu, Anca; Bonnet, Maryline; et al. (Inishmore Laser Scientific Publishing Ltd, 2023)
Abstract Background Tuberculosis preventive treatment (TPT) in child household contacts is recommended by World Health Organization (WHO) but limited data has been reported on the costs experienced by households with children receiving TPT. Methods We evaluated the economic impact on households with children receiving TPT within a service-delivery model cluster-randomised controlled trial in Cameroon and Uganda. The intervention included community health worker-led home-based child-contact screening, TPT initiation and monitoring, and referral of children with presumptive tuberculosis or side effects, and was compared with each country’s facility-based standard of care (control). We used a retrospective cross-sectional survey adapted from the WHO Global task force on tuberculosis patient cost surveys. All costs were collected between February 2021 and March 2021 and are presented in 2021 US$. Results The median household costs estimated using the human capital approach were higher in the control arm ($62.96 [interquartile range, IQR; $19.78-239.74] in Cameroon and $35.95 [IQR; $29.03-91.26] in Uganda) compared to the intervention arm ($2.73 [IQR; $2.73-14.18] in Cameroon and $4.55 [IQR; $3.03-6.06] in Uganda). Using a threshold of 20% of annual household income, 15% (95%CI; 5-31%) of households in Cameroon and 14% (95%CI; 4-26%) in Uganda experienced catastrophic costs in the control compared to 3% (95%CI; 1- 8%) in Cameroon and 3% (95%CI; 1-8%) in Uganda in the intervention. Using the output-based approach to estimate income losses increased costs by 14-32% in the control and 13-19% in the intervention across the two countries. The proportion of participants experiencing any dissaving was higher in the control, 53% (95%CI; 36-71%) in Cameroon and 50% (95%CI; 31-69%) in Uganda, compared to 18% (95%CI; 10-29%) in Cameroon and 17% (95%CI; 8-28%) in Uganda in the intervention. Conclusions Households with child contacts initiated on TPT under a facility-based model incur significant costs. Community-based interventions help to reduce these costs but do not eliminate catastrophic expenditures. Registration https://clinicaltrials.gov/ct2/show/NCT03832023.
Keywords: Tuberculosis, catastrophic cost, cost analysis, tuberculosis preventive therapy, social protection